Retention of Tegal Language as Introdoctury Language in Binlandik Kindergarten Level Kodim 0712 Tegal, Central Java - Jatut Yoga Prameswari; Dewi Indah Susanti; Siti Jubei (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
Regional languages have an important role in people's lives because their existence is highly respected by the state as one of national wealth. This paper aims to describe the understanding of the language of the Tegal area as the language of instruction at Binladik Kindergarten Level Unit Kodim 0712 Tegal, Central Java. This research is descriptive qualitative research and the method used is the literature method and the observation method. The results showed that Tegal language retention occurred in teaching and learning activities between teachers and students.